PENGARUH KEMAMPUAN KERJA DAN KREATIVITAS TERHADAP PRODUKTIVITAS PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN SUMENEP - jurnalmap map; Mathor ÔÇì; Indra Prasetyo; Fatimah Riswati (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT The purpose of this study is to study and discuss about work ability and creativity that are important together towards work productivity in the Sumenep Regency Communication and Information Agency; to know and understand whether it supports significant work and creativity towards work productivity at the Sumenep Regency Communication and Information Agency. This research is explanatory research with quantitive method. The population of this study amounted to 57 employees of the Communication and Informatics Office of Sumenep Regency, which at the same time was used as research samples. The results of the study describe simultaneously, work ability and employee creativity have a very significant importance on productivity. Partially, the work ability and creativity of employees have a significant importance on the productivity of the employees of the Communication and Informatics Office of Sumenep Regency, with employee creativity variables having the greatest influence on the productivity of the employees of the Sumenep Regency Communication and Information Office. Keywords: work ability, creativity, employee productivity